2009
DOI: 10.1073/pnas.0900960106
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunctions between metals and carbon nanotubes as ultimate nanocontacts

Abstract: We report the controlled formation and characterization of heterojunctions between carbon nanotubes and different metal nanocrystals (Fe, Co, Ni, and FeCo). The heterojunctions are formed from metal-filled multiwall carbon nanotubes (MWNTs) via intense electron beam irradiation at temperatures in the range of 450 -700°C and observed in situ in a transmission electron microscope. Under irradiation, the segregation of metal and carbon atoms occurs, leading to the formation of heterojunctions between metal and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 38 publications
2
101
0
Order By: Relevance
“…The controlled formation of heterojunctions between carbon nanotubes and different metal NCs ͑Fe, Co, Ni, and FeCo͒ was demonstrated. 358 The heterojunctions were formed from metal-filled MWNTs via intense electron beam irradiation in a TEM at elevated temperatures in the range of 450-700°C. Under irradiation, the segregation of metal and carbon atoms occurred, leading to the formation of heterojunctions between metal and graphite, Fig.…”
Section: Welding and Coalescence Of Carbon Nanotubes Under Electron Beammentioning
confidence: 99%
See 1 more Smart Citation
“…The controlled formation of heterojunctions between carbon nanotubes and different metal NCs ͑Fe, Co, Ni, and FeCo͒ was demonstrated. 358 The heterojunctions were formed from metal-filled MWNTs via intense electron beam irradiation in a TEM at elevated temperatures in the range of 450-700°C. Under irradiation, the segregation of metal and carbon atoms occurred, leading to the formation of heterojunctions between metal and graphite, Fig.…”
Section: Welding and Coalescence Of Carbon Nanotubes Under Electron Beammentioning
confidence: 99%
“…The inset shows a detail of the interface ͑white square͒ after noise filtering, where the bending of the nanotube layers to match the metal lattice is visible, from Ref. 358. ͑f͒ Junction between three MWNTs and a Co particle as made by electron irradiation of a metal-carbon nanotube composite.…”
Section: Engineering Carbon Nanostructures With a Focused Electron Beammentioning
confidence: 99%
“…The formation of CNTs could be attributed to the catalysis of iron particles and the decrease of vacuum degree in quartz tube during the cooling process. The grapheneCNTs system has significant technological advantages due to the combination of individual properties of graphene and CNTs in various applications (Kalita et al 2008;Rodríguez-Manzo et al 2009;Lee et al 2010;Zhang et al 2011).…”
Section: Fe-sem Analysismentioning
confidence: 99%
“…In the most widely used preparation process of chemical vapor deposition (CVD), the choice of transition metal catalyst particles provides a degree of control over the CNT morphology, the production yield, and the growth mode itself (base growth vs. tip growth) [21,22]. Consequently, the interface between the catalyst particle and the CNT is considered to play a key role for the CNT growth [17,[23][24][25][26]. Only few studies deal with the physical properties of these facets which are found to be particularly effective in dissociating the gaseous hydrocarbon feedstock during growth and which typically provide low activation energies for surface diffusion [17,27].…”
mentioning
confidence: 99%